History of Hypertension is The Most Influential Factor in Increasing The Occurrence of Preeclampsia in Lumajang Regency - Mutmainah Anggun Natungga; Iis Rahmawati; Muhammad Ihwan Narwanto (Jurnal Kesehatan dr. Soebandi, 2024)
Hypertensive disorders of pregnancy, including preeclampsia, are significant contributors to maternal mortality and morbidity globally. The study's objective was to investigate the most important factors that contribute to preeclampsia. in Lumajang Regency. The research design is a case-control study. The research location is at Rogorunan Health Center and Kunir Health Center.  The sample in this study was determined using saturated sample techniques or total sampling. samples at the Rogotrunan Health Center totaled 80 respondents and the Kunir Health Center which amounted to 75 respondents, totaling 155 respondents. Data collection using questionnaires. Analysis using logistic regression. The results of the study of variables that have a significant influence are on the variables of age (p-value = 0.070), history of hypertension (p-value = 0.000), pregnancy pause (p-value = 0.002), body mass index (p-value = 0.045), and hereditary hypertension (p-value = 0.000). A history of preeclampsia (p-value = 0.255) on the variable was excluded. Multivariate results between preeclampsia occurrence and history of hypertension obtained a value of p = 0.000, OR = 6.004 (1.549-5.065) meaning that The incidence of preeclampsia is influenced by a history of hypertension and history of hypertension affects 6.004 times the incidence of preeclampsia. Conclusion A history of hypertension is the most significant risk factor for preeclampsia, so the recommended advice is the importance of a healthy lifestyle, a balanced diet, exercise regularly, avoiding stress, avoiding smoking, not consuming harmful substances, monitoring blood pressure regularly, and regular treatment. All of these actions are a preventive effort so that during pregnancy preeclampsia does not occur.